Damage assessment of RC voided slabs experienced extreme fire flame. Issue 1 (February 2021) - Alawsi, Manal A.; Mhalhal, Jasim M.; Al-Gasham, Thaar S.; Abid, Sallal R.
Abstract: The main objective of this study was to assess the damage level in reinforced concrete voided slabs experimentally after exposure to high fire flame. Accordingly, four analogous slabs were created using the same concrete strength with dimensions of 500 mm long×270 mm wide×90 mm deep. They contained fifteen plastic balls with a 70 mm diameter, placed in between the top and bottom reinforcement meshes. Three specimens were subjected to direct fire flame using a diesel furnace at 200 °C, 500 °C, and 800 °C for one hour. The fourth was left without burning for the contrast purpose. Afterward, the slabs were tested under uniformly distributed loads up to collapse. The results indicated that the slabs' failure mode changed from combined flexural-shear to pure shear when the temperatures passed 200 °C. The residual strengths of 200-800 °C exposed slabs downed to 71.80% -52.00% relative to the unexposed one, respectively. As well, the ductility, service stiffness, and toughness of burned slabs remarkably decreased, approaching 65.97%, 54.18%, and 77.82%, respectively.